The Influence Of Ability And Work Discipline On The Implementation Of Iso 9001 At Akpelni Vocational Shipping School Semarang - Budi Purnomo; Ratna Kurnia Dewi; Haris Padilah; Haryani Haryani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Every organization is required to be able to optimize existing resources within the organization, especially human resources. Human resource management must be distinct from employees expected to perform as well as possible to achieve organizational goals. This research was conducted at Akpelni Vocational School, Semarang, to determine the influence of work discipline, and workability on ISO 9001. The sample used in the research was 70 respondents. The data obtained was processed using descriptive analysis and quantitative statistical analysis. Quantitative analysis uses multiple regression analysis to determine the effect of the independent variable on the dependent variable, but before carrying out this test, a validity and reliability test and a requirements test are carried out. The research results show that work discipline and workability influence ISO 9001 at SMK Akpelni Semarang..